Greater regional cortical gray matter thickness in obsessive-compulsive disorder - Narayan, Veena M. (2008)
Earlier studies are inconsistent regarding the structural basis of obsessive-compulsive disorder (OCD), and few studies have investigated whether patients with OCD have cortical thickness abnormalities compared with healthy volunteers. Using magnetic resonance imaging we compared regional differences in cortical thickness among 21 patients with OCD and 21 demographically matched healthy volunteers. Our findings indicate that the right inferior frontal cortex and posterior middle temporal gyrus are thicker in patients with OCD compared with healthy controls, which may contribute to response inhibition deficits and other aspects of phenomenology related to the disorder.